2020
DOI: 10.1038/s41467-020-14626-0
|View full text |Cite
|
Sign up to set email alerts
|

Influenza A viruses are transmitted via the air from the nasal respiratory epithelium of ferrets

Abstract: Human influenza A viruses are known to be transmitted via the air from person to person. It is unknown from which anatomical site of the respiratory tract influenza A virus transmission occurs. Here, pairs of genetically tagged and untagged influenza A/H1N1, A/H3N2 and A/H5N1 viruses that are transmissible via the air are used to co-infect donor ferrets via the intranasal and intratracheal routes to cause an upper and lower respiratory tract infection, respectively. In all transmission cases, we observe that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
120
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 152 publications
(128 citation statements)
references
References 50 publications
(102 reference statements)
7
120
0
1
Order By: Relevance
“…This potential is further bolstered by the observation that a COVID-19 patient with distinct populations of SARS-CoV-2 in throat swabs and sputum samples only transmitted the throat strain 26 . Similar nasal-driven transmission was recently reported for human influenza A virus in ferrets 30 . However, age-dependent impacts of D614G on SARS-CoV-2 infection, pathogenesis, and transmission remain to be studied.…”
Section: Discussionsupporting
confidence: 87%
“…This potential is further bolstered by the observation that a COVID-19 patient with distinct populations of SARS-CoV-2 in throat swabs and sputum samples only transmitted the throat strain 26 . Similar nasal-driven transmission was recently reported for human influenza A virus in ferrets 30 . However, age-dependent impacts of D614G on SARS-CoV-2 infection, pathogenesis, and transmission remain to be studied.…”
Section: Discussionsupporting
confidence: 87%
“…Also, all four macaques expressed SARS-CoV-2 antigen in mucous glands of the nasal cavity at day 4 p.i., which was not seen for SARS-CoV (9)(10)(11) or MERS-CoV infections (this manuscript) in this animal model. Viral tropism for the nasal mucosa fits with efficient respiratory transmission, as has been seen for influenza A virus (18). SARS-CoV-2 was primarily detected in tissues of the respiratory tract, however SARS-CoV-2 RNA was also detectable in other tissues such as intestines, in line with a recent report (19).…”
Section: Main Textsupporting
confidence: 87%
“…The efficiency of transmission via the air depends on the anatomical site of virus excretion, the amount and duration of infectious virus shedding in the air, the ability of the virus to remain infectious in the air, and the infectious dose required to initiate an infection in an individual. It was recently shown that influenza A viruses are transmitted via the air from the nasal respiratory epithelium of ferrets 30 . In the current study, SARS-CoV and SARS-CoV-2 RNA was detected in nose and throat swabs of all infected ferrets.…”
Section: Discussionmentioning
confidence: 99%